Speaking, Playing, Learning: Unveiling the Potential of Role Playing Models in Differentiated Elementary Education - Zaenatul Wasilah; Sri Sukasih (Universitas Pendidikan Ganesha, 2024)
Students' lack of confidence in speaking skills in primary schools is often caused by a lack of exposure, active practice, and learning approaches that do not support students' diverse learning styles. This hurts the development of their speaking skills. So, this study aims to evaluate the effectiveness of role-playing models in differentiated learning on speaking skills and learning outcomes of grade IV students in elementary school. This study used a quasi-experimental method with a nonequivalent control group design, involving 56 grade IV students as samples. The data collection methods used were tests and observations using research instruments like tests and observation sheets. After the data was collected, it was analyzed using an independent sample t-test. The results showed that role-playing models significantly improved students' speaking skills and learning outcomes compared to the conventional method. So, it can be concluded that the role-playing model is efficacious in improving students' speaking skills and learning outcomes. This study's results significantly contribute to developing more innovative and needs-oriented learning strategies for students.